2003
DOI: 10.1029/2002gl016154
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and sources of multidecadal oscillations in drought‐sensitive tree‐ring records from the central and southern Rocky Mountains

Abstract: Tree‐ring records spanning the past seven centuries from the central and southern Rocky Mountains were studied using wavelet analysis to examine multidecadal (>30–70 yr) patterns of drought variation. Fifteen tree‐ring series were grouped into five regional composite chronologies based on shared low‐frequency behavior. Strong multidecadal phasing of moisture variation was present in all regions during the late 16th century megadrought. Oscillatory modes in the 30–70 yr domain persisted until the mid‐19th centu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 20 publications
8
138
0
1
Order By: Relevance
“…2 B and E). Previous research has shown that, during positive AMO conditions, the central U.S. receives below-average precipitation, particularly during summer (1,8). The large positive correlations between smoothed AMO and drought frequency for the central U.S. (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…2 B and E). Previous research has shown that, during positive AMO conditions, the central U.S. receives below-average precipitation, particularly during summer (1,8). The large positive correlations between smoothed AMO and drought frequency for the central U.S. (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Such long-term forecasts could help water managers plan for persistent drought across the conterminous United States (1). The urgency for such planning became evident when much of the U.S. was gripped by drought in 1996 and again in 1999-2003, evoking images of the dry 1930s and 1950s.…”
mentioning
confidence: 99%
“…Recently, research efforts have pointed to the Atlantic Ocean as a source of information to explain significant amounts of the D2M variability in North American, and possibly, global climate (Enfield et al, 2001;Gray et al, 2003Gray et al, , 2004Hodson, 2003, 2005;McCabe and Palecki, 2006). For example, the AMO has a strong relation to summer rainfall over the conterminous US, and may modulate the strength of the teleconnection between ENSO and winter precipitation (Enfield et al, 2001).…”
Section: Variability Of Sea-surface Temperatures and North American Hmentioning
confidence: 99%
“…More recently, research efforts have pointed to the Atlantic Ocean as a source of information to explain significant amounts of the variability in North American, and possibly, global climate (Enfield et al, 2001;Gray et al, 2003;Sutton and Hodson, 2003;Sutton and Hodson, 2005). For example, the AMO has a strong relation to summer rainfall over the conterminous United States, and may modulate the strength of the teleconnection between ENSO and winter precipitation (Enfield et al, 2001).…”
Section: Introductionmentioning
confidence: 99%